Identification and characterization of B-cell epitopes of IpaC, an invasion-associated protein of Shigella flexneri. - Phalipon, A (1992)
Invasion plasmid antigen C (IpaC) is a 43-kDa plasmid-encoded protein associated with the ability of shigellae to invade epithelial cells. This protein is consistently strongly recognized by sera from convalescent patients and monkeys experimentally infected with shigellae. The strong immunogenicity of IpaC in the course of natural infection makes it a good candidate as a potentially protective antigen. To map the B-cell epitopes of this protein, the gene encoding IpaC was cloned and expressed at a high level in Escherichia coli. The partially purified recombinant protein was used to raise rabbit polyclonal antisera and murine monoclonal antibodies. A lambda gt11 ipaC gene library was screened with the antisera and antibodies. Recombinant DNA clones producing specific antigenic determinants were isolated, and the sequence of their DNA inserts was determined. The amino acid sequence of each determinant was deduced from the minimal overlap of DNA inserts of multiple antibody-positive DNA clones. Two distinct epitopes, located between amino acid residues 25 and 33 and 90 and 97, were identified. Two additional B-cell epitopes which were located between residues 297 and 349, near the carboxy-terminal end of the protein, were characterized. Each of these epitopes was also recognized by sera from convalescent humans and monkeys. Therefore, it seems likely that these epitopes are relevant to the humoral response against IpaC during natural infection.